A Study of the Impact of PSAK 71 Implementation on Financial Performance and Capital Adequacy Ratio - Maulidha, Veny Eka; Kusumah, R. Wedi Rusmawan (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
This study intends to compare bank financial performance in terms of net income before and after applying PSAK 71 to CKPN in terms of bank credit, capital, and financial performance. This research employs quantitative data in the form of published bank financial statements and the bank's financial ratios to analyze the impact of the new PSAK 71. The results of this study show that PSAK 71 adoption has a favorable effect and that it can provide useful data for financial report users to estimate total, period, and future cash flow uncertainty. However, there are some adverse effects, such as a rise in CKPN and a decrease in KPPM (or Capital Adequacy Ratio). The CKPN will rise by up to 50%, while the KPPM will fall by 5%. Because the decrease of CKPN could have an impact on the Bank performance and there will be more risk to be managed by the Bank, it is crucial for the Bank to make solid preparations from the strategic viewpoint, technical, and operational side.